PENGARUH KUALITAS PELAYANAN, SANKSI, BIAYA KEPATUHAN DAN KEMUDAHAN E-FILLING TERHADAP KEPATUHAN WAJIB PAJAK - Fitriana Mawaddah; Rizka Ramayanti (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2022)
MSME tax is one of the national development sources. This study aimed to evaluate whether service quality, tax sanctions, compliance costs, and the usability of e-filing had an effect on MSME taxpayer compliance. This investigation was done by 44 Depok-based SMB respondents. Utilizing Partial Least Square, the SmartPLS application conducts data analysis. This study reveals that the quality of tax services, tax sanctions, and the convenience of e-filing have an effect on taxpayer compliance, however the cost of compliance has no effect. Keywords: Compliance costs; tax sanctions; tax service quality; ease of use of e-filling